Bilateral psoas abscesses and vertebral osteomyelitis in a patient with sickle cell disease. (21st September 2010) - Asnani, M; Williams, E W; Cawich, S; Reid, M; Mansingh, A; Shah, S; Williams-Johnson, Jean
Abstract : The authors present a case of a patient with sickle-β thalassaemia (Sβ 0 Thal) who had bilateral psoas abscesses on a background of splenectomy in early childhood. The patient also turned out to have vertebral osteomyelitis and hydronephrosis on the side of the larger abscess. The only organism recovered from the patient was a Bacteroides species. The patient was managed with percutaneous drainage and intravenous antibiotics and made a full recovery.